2004
DOI: 10.1007/s11104-005-4292-y
|View full text |Cite
|
Sign up to set email alerts
|

Zea mays L. amylacea from the Lluta Valley (Arica-Chile) tolerates salinity stress when high levels of boron are available

Abstract: Elevated levels of boron occurring naturally in soil or irrigation waters are detrimental to many crops grown in agricultural regions of the world. If such levels of boron are accompanied by conditions of excessive salinity, as occurs in the Lluta valley in Northern Chile, the consequences can be drastic for crops. A variety of sweet corn from this valley (Zea mays L. amylacea) has arisen as a consequence of practiced seed selection, suggesting that it is extremely tolerant to high salt and boron levels. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
63
0
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 58 publications
9
63
0
7
Order By: Relevance
“…The close relationship between P N and Na + concentration in leaf tissue was reported by Iqbal and Ashraf (2005), indicating that P N was affected by Na + in the leaf mesophyll. Salinity-induced excessive accumulation of Na + in the leaves of plants which was also obtained in the present study ( Figure 2); it is in agreement with the opinion that high accumulation of Na + in the cytoplasmor chloroplast can affect the integrity and function of photosynthetic membranes, when the vacuole can no longer sequester toxic ions (Bastías et al 2004). Moreover, the reduced photosynthesis at high salinity could be also attributed, in part, to the reduced content of K + (Figure 2) which is indispensable in maintaining the steady-state photosynthetic rate and contributes to better regulation of stomata opening (Stępień and Kłbus 2006).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The close relationship between P N and Na + concentration in leaf tissue was reported by Iqbal and Ashraf (2005), indicating that P N was affected by Na + in the leaf mesophyll. Salinity-induced excessive accumulation of Na + in the leaves of plants which was also obtained in the present study ( Figure 2); it is in agreement with the opinion that high accumulation of Na + in the cytoplasmor chloroplast can affect the integrity and function of photosynthetic membranes, when the vacuole can no longer sequester toxic ions (Bastías et al 2004). Moreover, the reduced photosynthesis at high salinity could be also attributed, in part, to the reduced content of K + (Figure 2) which is indispensable in maintaining the steady-state photosynthetic rate and contributes to better regulation of stomata opening (Stępień and Kłbus 2006).…”
Section: Discussionsupporting
confidence: 93%
“…Significant reduction of RWC in leaves of plants treated with 400 and 600 mmol/l (Figure 1) indicated that salinity also resulted in dehydration at cellular level and dehydration symptoms were greater in higher NaCl concentration treatment because of the increasing cellular water loss. Ion uptake is the cheapest form of osmotic adjustment under soil saline conditions, but it could also lead to problems of decline in leaf function and ionic imbalance and toxicity (Bastías et al 2004, Yildirim et al 2009). In particular, salinity alters uptake and absorption rates of all mineral nutrients resulting in deficiency symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similares resultados fueron reportados por Edelstein et al (2005) trabajando con plantas de melón y CE de 1,8 y 4,6 dS m -1 y concentraciones crecientes de boro hasta 10 mg L -1 . Bastías et al (2004) e Ismail (2003 obtuvieron resultados similares trabajando con plantas de maíz y concentraciones de boro de hasta 40 mg kg -1 en el suelo, viéndose disminuido el efecto tóxico del boro con concentraciones de NaCl superiores a 100 mM. Los resultados obtenidos con este ensayo sólo muestran un efecto tampón de la salinidad sobre el exceso de boro en la concentración de sólidos solubles de los frutos, mientras que en el resto de los parámetros medidos la combinación de salinidad con boro resulta en un aumento no significativo de los valores por sobre los valores del tratamiento T2 (exceso de boro).…”
Section: Resultados Y Discusiónunclassified